Health in Early Adolescence and Paid Employment. Issue 3 (April 2022) - Bozick, Robert; Sastry, Narayan; Liu, Airan
This study examines the relationship between health and adolescent employment. Using data from the Panel Study of Income Dynamics' Child Development Supplement and Transition into Adulthood Supplement, we examine a cohort of 2, 925 youth who were followed from childhood into adolescence. We focus on two outcomes measured when sample members were ages 16, 17, and 18: employment status and average weekly hours worked. With these data, we test the hypothesis that youth with health conditions will be less likely to work and if they do work, they work fewer hours a week. We find mixed support for this hypothesis. Youth with sensory limitations, developmental disabilities, and externalizing problem behaviors are less likely to work than their peers without these conditions. However, conditional on being employed, youth with externalizing problem behaviors and ADHD work more hours a week than their peers without those conditions.